'My friends would laugh at me': embedding the dominant heterosexual script in the talk of primary school students. Issue 3 (3rd April 2022) - Morison, Tracy; Macleod, Catriona Ida; Lynch, Ingrid
ABSTRACT: The dominant 'heterosexual script' positions men as sexually desiring subjects who initiate sex and use active displays of power to attract women, and women as passive sexual objects who use indirect means to attract men (e.g. physical appearance). While much research has highlighted how this script is deployed in high school settings, less work has attended to primary schools. We demonstrate how the script operates in the talk of primary school students in low resource South African schools. Data were generated in group discussions conducted for a mid-term review of a school-based sexual violence prevention programme. We show how the heterosexual script is embedded in students' accounts through the regulatory mechanisms of interpersonal and social risks: threats of being 'dumped', sexual coercion, violence, and humiliation. These risks are learnt from an early age and may outweigh sexuality education messaging provided later on, which has implications for such interventions. To address this we advocate for early engagement with young people using a dialogical approach that creates a relational context for resistance to inequitable sexual scripts.